Analisis karakteristik aerodinamika telescopic wing dengan konfigurasi sayap flying wing dan glider menggunakan metode pendekatan simulasi CFD - Azmi, Azhim Asyratul; Hariyanto, Satriawan Dini; Hidayat, Arif (Universitas Muhammadiyah Metro, 2021)
A telescopic wing is a shape-changing method of the aircraft wing known as the morphing wing system. Wingspan extends capability on telescopic wing increasing the aspect ratio to get a high lift force. The telescopic wing on a flying wing configuration as an external wing and glider wing as an internal wing can be used to increase the coefficient lift (CL) when carrying out special missions. The aerodynamic characteristics using the Computational Fluid Dynamic (CFD) simulation approach is presented. For the 40% internal wingspan, the highest CL increment was 12.9% at a 10o angle of attack. For the 50% internal wingspan, the highest CL increment was 14.9% at a 10o angle of attack. on the 40% internal wing, the highest coefficient drag (CD) increment was 4.7%, and the largest CD increment on 50% internal was 9.5% at the angle of attack of 20o. The pressure distribution along the internal wingspan was uneven from an angle of attack of 15o due to the wing tip vortices of the external wing. Streamline pattern shown a bubble separation from the leading edge at an internal wing root by external wing tip vortices.Keywords: Morphing wing, telescopic wing, flying wing, glider